2022
DOI: 10.1002/admi.202200822
|View full text |Cite
|
Sign up to set email alerts
|

In Situ‐Formed LiF‐Rich Multifunctional Interfaces toward Stable Li10GeP2S12‐Based All‐Solid‐State Lithium Batteries

Abstract: Li10GeP2S12 (LGPS) solid electrolyte with extremely high ionic conductivity is a promising candidate for all‐solid‐state lithium batteries. However, continued LGPS reduction at Li/LGPS interface is huge challenge. Thus, developing a simple and effective strategy to improve Li/LGPS interfacial stability is highly urgent. Herein, LiF‐rich multifunctional interfaces on Li metal (Li@LiF), consisting of three functional components of LiF, carbon particles, and thin CF bond top‐layer, are in situ constructed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Shen et al. [ 223 ] built an LiF‐rich layer on Li anode surface to improve the interfacial stability between Li and LGPS via a spontaneously reaction of lithium and poly(tetrafluoroethylene). In addition, Chen et al.…”
Section: Surface Modification Of Anode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shen et al. [ 223 ] built an LiF‐rich layer on Li anode surface to improve the interfacial stability between Li and LGPS via a spontaneously reaction of lithium and poly(tetrafluoroethylene). In addition, Chen et al.…”
Section: Surface Modification Of Anode Materialsmentioning
confidence: 99%
“…The enhanced contact area and unique structure decreased the local current density and generated stable interphase. Shen et al [223] built an LiF-rich layer on Li anode surface to improve the interfacial stability between Li and LGPS via a spontaneously reaction of lithium and poly(tetrafluoroethylene). In addition, Chen et al [224] adopted the ultrathin poly[2,3-bis(2,2,6,6tetramethylpiperidine-N-oxycarbonyl)-norbornene](PTNB) polymer coating layer on Li metal anode to avoid the structure failure of LATP when it contacted to Li metal.…”
Section: Surface Modification With Ceramic Materialsmentioning
confidence: 99%
“…Zhang et al developed a LiF-rich multifunctional interphase with a thickness of around 3 μm on Li metal anode of LGPSbased SSLMBs. [162] The artificial interphase consisted of LiF, amorphous carbon particles, and CÀ F bond. The LiF could block the synergistic effect of the composite SSEs and the coated artificial SEI layer.…”
Section: The Interfacial Issue In the Solid-state Electrolytes (Sses)mentioning
confidence: 99%
“…Zhang et al. developed a LiF‐rich multifunctional interphase with a thickness of around 3 μm on Li metal anode of LGPS‐based SSLMBs [162] . The artificial interphase consisted of LiF, amorphous carbon particles, and C−F bond.…”
Section: The Interfacial Issue In the Solid‐state Electrolytes (Sses)mentioning
confidence: 99%
“…17 So far, constructing a protective layer is a viable strategy to strengthen the Li 10 GeP 2 S 12 /lithium metal interface. For example, research studies have demonstrated an improved interface stability by introducing Li 3 PO 4 , 18 LiF, 19 and BN 20 layers at the Li 10 GeP 2 S 12 /lithium metal interface. In addition, alloys such as Li−Ag 21 and Li−Mg 22 have also been used as a buffer layer to provide effective protection for Li 10 GeP 2 S 12 .…”
Section: Introductionmentioning
confidence: 99%